The factors that influence the natural gas price in United States / Siti Azura Mohd Sawal (Faculty of Business and Management, 2007)
The fluctuation of natural gas price in United States has raise major concern among the industry player and the consumer itself. Increasing in the price of natural gas last few years is influence by several factors. Natural gas is a vitally important source of energy for all sectors of the economy in the United States. There are several factors that influence supply and demand, such as storage, seasonality, weather, production disruptions and oil prices. The purpose of this study is to verify the factors that influence the price of the natural gas in United States. Furthermore, it is also conduct in order to identify the effect of the factors to the price of the natural gas in United States. This study is using exploratory and descriptive research design. Moreover, the study is also using secondary data instead of primary data. Secondary data used due to the difficulty in gathering primary data. Internet, books, magazines and past research have been used in understanding the natural gas prices in United States. There are four type of analysis in SPSS program that had been used in the study to analyze the data including frequency table, cross tabulation, correlation and regression. In addition, to achieve the second objective, the study is using the Microsoft Excel. The study is done in order to find the factors that influence the natural gas price in United States. Beside that, the study is also done to explain about the effect of the factors to the natural gas price.